Typification of the name Hippocrepis balearica (Leguminosae) - Ferrer Gallego, Pedro Pablo; Sáez, Llorenç (Mediterranean Botany, 2022)
The typification of the name Hippocrepis balearica is discussed. The name is lectotypified on an illustration published by Jacquin in 1781.